INFLUENCE OF AMBIENT TEMPERATURE ON STIFFNESS OF ASPHALT PAVING MATERIALS (Journal of Engineering, 2011)
Asphalt pavement properties in Iraq are highly affected by elevated summer air temperatures. One of these properties is stiffness (resilient modulus). To explain the effect of air temperatures on stiffness of asphalt concrete, it is necessary to determine the distribution of temperatures through the pavement asphalt concrete layers. In this study, the distribution of pavement temperatures at three depths (2cm,7cm, 10cm) below the pavement surface is determined by using the temperature data logger instrument. A relationship for determining pavement temperature as related to depth and air temperature has been suggested. To achieve the objective of this thesis, the prepared specimens have been tested for indirect tension in accordance with ASTM D4123, using the pnuematic repeated load apparatus, in order to determine the values of resilient modulus at three different temperatures (10, 25, 40) °C. From results of testing, it is observed that the resilient modulus decreases with increase in test temperature by a rate of 8.78×10 Psi/C' for asphalt concrete wearing courses. An increase in optimum asphalt content by 0.1% (by weight of total mixture) causes a decrease in resilient modulus by 22% at a temperature of 40C". A statistical model for the prediction of resilient modulus has been developed depending on mixture variables of: asphalt content, asphalt hinder viscosity, surface area of combined aggregates, air voids of compacted mixture and test temperature.